Cell-Intrinsic Roles for Autophagy in Modulating CD4 T Cell Functions - Jacquin, Elise; Apetoh, Lionel (Frontiers in Immunology, 2018)
The catabolic process of autophagy plays important functions in inflammatory and immune responses by modulating innate immunity and adaptive immunity. Over the last decade, a cell-intrinsic role for autophagy in modulating CD4 T cell functions and differentiation was revealed. After the initial observation of autophagosomes in effector CD4 T cells, further work has shown that not only autophagy levels are modulated in CD4 T cells in response to environmental signals but also that autophagy critically affects the biology of these cells. Mouse models of autophagy deletion in CD4 T cells have indeed shown that autophagy is essential for CD4 T cell survival and homeostasis in peripheral lymphoid organs. Furthermore, autophagy is required for CD4 T cell proliferation and cytokine production in response to T cell receptor activation. Recent developments have uncovered that autophagy controls CD4 T cell differentiation and functions. While autophagy is required for the maintenance of immunosuppressive functions of regulatory T cells, it restrains the differentiation of TH9 effector cells, thus limiting their antitumor and pro-inflammatory properties. We will here discuss these findings that collectively suggest that therapeutic strategies targeting autophagy could be exploited for the treatment of cancer and inflammatory diseases.